One-week sleep hygiene education improves episodic memory in young but not in older adults during social isolation - Tassone, Leonela Magali; Moyano, Malen Daiana; Laiño, Fernando; Brusco, Luis Ignacio; Ramele, Rodrigo Ezequiel; Forcato, Cecilia (Frontiers in Psychology, 2023)
Memory formation is a dynamic process that comprises different phases, such as encoding, consolidation and retrieval. It could be altered by several factors such as sleep quality, anxiety, and depression levels. In the last years, due to COVID-19 pandemic, there was a reduction in sleep quality, an increase in anxiety and depressive symptoms as well as an impairment in emotional episodic memory encoding, especially in young adults. Taking into account the profound impact of sleep quality in daily life a series of rules has been developed that are conducive to consistently achieving good sleep, known as sleep hygiene education. These interventions have been shown to be effective in improving sleep quality and duration and reducing depressive and anxiety symptoms. Here we propose the implementation of a brief sleep hygiene education to improve sleep quality and memory performance as well as to diminish anxiety and depressive scores. For that, participants were divided into two groups: Sleep hygiene education and control group. After that, they were evaluated for anxiety, depression, and sleep quality levels and trained on an episodic memory task. They were tested immediately after (short-term test) and also one week later (long-term test). This procedure was also performed before the sleep hygiene education and was taken as baseline level. We found that episodic memory performance for young adults improved for the SHE group after intervention but not for older adults, and no improvements in emotional variables were observed. Despite not observing a significant effect of the intervention for young and older adults regarding the sleep quality scores, we consider that there may be an improvement in sleep physiology that is not subjectively perceived, but would also have a positive impact on memory processes. These results show that even a sleep hygiene education of one week could improve cognition in young adults when acute memory and sleep impairment occurs, in this case, due to the isolation by COVID-19 pandemic.However, we suggest that longer interventions should be implemented for older adults who already experience a natural decline in cognitive processes such as episodic memory formation.